International sanctions and limits of lerner symmetry - Itskhoki, Oleg and Mukhin, Dmitry (AEA Papers and Proceedings)
After a wave of globalization, trade wars and financial sanctions again become frequent tools of international policymaking, leading to an increased interest in the consequences and effectiveness of international sanctions. Itskhoki and Mukhin (2022b) show that Lerner symmetry provides an important benchmark with import and export sanctions equivalent in terms of their effects on allocations and welfare. This abstracts from several practical issues, including the timing of sanctions, interactions between trade and financial restrictions, and the effects of sanctions on the financial sector. We incorporate these features to study their implications and emphasize points of departure from Lerner symmetry.- Reproduced